Collectio Mineralium The catalog of Holy Roman Emperor Leopold II's mineralogical collection - Franza, Annarita; Mattes, Johannes; Pratesi, Giovanni (Cataloghi e collezioni, 2022)
This work is the critical edition of the catalog of Holy Roman Emperor Leopold's II mineralogical collection. The volume, unpublished and preserved at the Historical Archives of the University of Firenze Museum System, dates to 1765 and describes 242 mineralogical specimens coming primarily from the current Slovak-Hungarian mining district. This edition gives the transcription of the German manuscript and its translation into English together with an organized system of notation to illustrate the complex history of the text, the characterization of the mineralogical species, and the geographical location of the mineral extraction sites. This work represents to date the only published catalog of a mineralogical collection belonging to a member of the Habsburg-Lorraine family.